Increased in vitro Cell Proliferation by Chitosan/pGM-CSF Complexes - (:unkn) unknown (INDIAN PHARMACEUTICAL ASSOC, 2011)
Granulocyte macrophage colony stimulating factor, a potent hematopoietic cytokine, has been shown to stimulate production of white blood cells following chemotherapy. Therefore, the granulocyte macrophage colony stimulating factor gene is a potential candidate for the treatment of different pathological conditions. The purpose of this study is to investigate the suitability of chitosan as carrier for pORF-hGMCSF plasmid encoding granulocyte macrophage colony stimulating factor gene and also to study the effect of complexes on protein production and cell proliferation. Chitosan/pGM-CSF complexes were prepared using different (+/-) ratios (from 0.01/1 to 5/1). Complex formation was checked with agarose gel electrophoresis. The size and zeta potential values were measured. Enzyme and serum stability of complexes were studied. In vitro transfection properties of complexes were studied in HeLa cells. According to agarose gel electrophoresis, full complexation was obtained at 0.1/1 and higher chitosan/pGM-CSF ratios. Complexes having about 132 nm size and +13.7 mV zeta potential value were obtained. Chitosan complexes protected plasmid against enzymatic and serum effects. The gene expression-dependent cell proliferation after transfection of chitosan/pGM-CSF complexes at 72 h was markedly increased in comparision with the level of control group. These results indicate that the effect of chitosan/pGM-CSF complexes on cell proliferation was changed with N/P ratio and time-dependently. For GM-CSF therapy, chitosan/pGM-CSF complexes may be used as alternative to conventional protein treatments. Chitosan may be a good carrier for pORF-hGMCSF. Further, in vivo study is ongoing.
Keywords: Chitosan; cell proliferation; MTT; pGM-CSF; COLONY-STIMULATING FACTOR; GENE DELIVERY-SYSTEM; MOLECULAR-WEIGHT; PLASMID-DNA; TRANSFECTION EFFICIENCY; VACCINE; GROWTH; NANOPARTICLES; MICROSPHERES; EXPRESSION